2015
DOI: 10.1515/bog-2015-0008
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Regulation of Residential Suburbanisation in Hinterland of Post-socialist ‘One Hundred Thousands’ City of České Budějovice

Abstract: Residential suburbanisation is currently the most important urbanisation process transforming metropolitan areas in European post-socialist countries, especially in Central Europe and at Baltic states. The paper compares the statements of the mayors of the suburban municipalities situated in the hinterland of the city of České Budějovice (a one-hundred-thousand city in the South-West of the Czech Republic) and also the local building officials, spatial planning ofcials and experts regarding the recent, current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 58 publications
1
21
0
1
Order By: Relevance
“…The results of this study corroborate previous findings reported for other post-communist cities in Central and Eastern Europe such as Tallinn (Tammaru et al, 2009), České Budějovice (Kubeš, 2015), Riga (Krišjāne et al, 2012), Vilnius (Burneika, Ubarevičienė, 2011) and Brno (Sýkora, Ouřed-níček, 2007 …”
Section: Discussionsupporting
confidence: 91%
“…The results of this study corroborate previous findings reported for other post-communist cities in Central and Eastern Europe such as Tallinn (Tammaru et al, 2009), České Budějovice (Kubeš, 2015), Riga (Krišjāne et al, 2012), Vilnius (Burneika, Ubarevičienė, 2011) and Brno (Sýkora, Ouřed-níček, 2007 …”
Section: Discussionsupporting
confidence: 91%
“…Another solution in the development of suburban communities is to create a green belt that will activate a new element in the suburban landscape and fulfil an environmental and socio-economic function in the ecosystem of local services, such as mobility, water supply, recreation and culture [108]. On the other hand, in many countries, there is no wider territorial regional planning, but Kubeš [109] considers the lack of metropolitan planning for more local and regional authorities to be explicitly inappropriate and impractical. Individual municipalities should pay attention not only to monitoring the impact of the suburbanisation process on the municipality and its functioning [13], but also to creating regulations that will guide development [13,73].…”
Section: Discussionmentioning
confidence: 99%
“…2012 -Polish Olsztyn;Novotný, L. 2012 -Slovakian Košice). After the strong development of the first decade of the new millennium, residential suburbanisation has weakened somewhat in this region due to the previous strong development, the ongoing economic crisis and the ending population shrinking of cities (Haase, A. and Rink, D. 2015;Kubeš, J. 2015a).…”
Section: Introductionmentioning
confidence: 99%